Preservation and sterilization methods of the meniscal allografts: literature review - Mickiewicz, Patrycja (Springer Netherlands, 2013)
Nowadays, there are four types of meniscal allografts known: fresh, cryopreserved, deep-frozen and lyophilized ones but only two of them are widely used in clinical practice. Use of different types of meniscal allografts still remains controversial due to preparation method, their biomechanical properties as well as cost which is connected with processing and storage. The main aim of this review is to present the current status of knowledge concerning meniscal allograft preservation and sterilization, especially the advantages and disadvantages of each method. Authors wanted to show a broad spectrum of methods used and conceptions presented by other authors. The second aim is to gather available information about meniscal preservation and sterilization methods in one paper. Deep-frozen and cryopreserved meniscal allografts are the most frequently used ones in the clinical practice. The use of fresh grafts stays controversial but also has many followers. Lyophilized grafts in turn are not applied at present due to some serious drawbacks including reduction of tensile strength, poor rehydration, graft shrinkage and post-transplantation joint effusion as well as increased risk of meniscal size reduction. An application of sterilizing agents make the meniscal allograft free from the bacteria and viruses, but also it may cause serious structure changes. Therefore, choosing just one ideal method of meniscal allograft preservation and sterilization is complicated and should be based on broad knowledge and experience of surgeon performing the transplantation.